A genus‐level phylogenetic linear sequence of monocots. Issue 3 (27th May 2015) - Trias-Blasi, Anna; Baker, William J.; Haigh, Anna L.; Simpson, David A.; Weber, Odile; Wilkin, Paul
Abstract: This paper provides an up‐to‐date linear sequence of monocot families and genera (excluding Orchidaceae and Poaceae) based on current phylogenetic evidence. The sequence is provided in a numbered list of each of the 1225 genera in 75 monocot families, together with a complementary alphabetical list. The sequence represents a standardized tool for the organisation of monocot herbarium collections.